BUDAYA KOMUNIKASI SUKU BUGIS DAN SUKU MANDAR DI SMP NEGERI 1 PASANGKAYU PROVINSI SULAWESI BARAT (KAJIAN ETNOGRAFI KOMUNIKASI) - Ilham, Musdalifa A.; Suputra, I Gusti Ketut Alit; Tahir, Moh. (BAHASANTODEA, 2017)
There are 2 main problems of this research such as: how is the form of communication culture of Bugis and Mandar tribe in SMP Negeri 1 Pasangkayu?, and hos is the speech strategy of Bugis and Mandar tribe in SMP Negeri 1 Pasangkayu? Data were collected through taking note and listening method using tapped technique. Data were analyzed using four stages: data collection, data reduction, data presentation, and conclusion or verification. Furtheremore, the result of this research revelas 9 communication form they are: 1) command form, 2) suggest form, 3) complain form, 4) invite form, 5) ask form, 6) congratulate form, 7) apologize form, 8) joke form, and 9) promise form. Meanwhile, there are 8 direct speech strategy such as: 1) direct command strategy, 2) direct suggest strategy, 3) direct compalin startegy, 4) direct invite strategy, 5) direct ask strategy, 6) direct congratulate strategy, 7) direct apologize strategy, and 8) direct promise strategy. There are also 6 undirect speech strategy: 1) indirect command strategy, 2) indirect suggest strategy, 3) indirect compalin startegy, 4) indirect invite strategy, 5) indirect ask strategy, 6) indirect apologize strategy.